A micro-level transport model for plant-based food materials during drying. (21st September 2018) - Rahman, M.M.; Kumar, Chandan; Joardder, Mohammad U.H.; Karim, M.A.
Highlights: A novel microstructure based food drying model for plant based food material has been developed. The model can predict cellular level temperature and moisture distribution. The model is validated with experimental results obtained from X-ray micro CT experiemnts. The impact of cell and intercellular space in the drying process has been investigated. Abstract: Microscale transport phenomena govern the overall transport mechanism during drying of plant-based food material. However, there is limited research available that considers micro-level transport phenomena during drying. The primary goal of this work is to develop a microscale drying model based on the heterogeneous microstructure of the plant-based food materials to predict cellular-level water transport mechanism during drying. The microstructure, which was used as a heterogenous computational domain for the model, was developed from scanning electron microscope images of food samples. Simulation results show that moisture transport and distribution are significantly affected by the characteristics of cells, the intercellular spaces and the cell walls. The predicted moisture profile from the developed model was compared with results obtained by X-ray microtomography (µCT), and a good agreement was found. The model and the experimental results also confirmed that a water gradient (2–3%) still existed in the dried sample around the walls of the cells that are located at the centre of the tissue. The micro-level temperature distribution in the cells and intercellular spaces was also successfully predicted. It was found that the air-filled intercellular spaces were heated faster than the cells during drying. Sensitivity studies were performed to investigate the influence of the key drying parameters on the micro-level transport process. The developed model accurately reflects the micro-level transport phenomena that occur during drying.